Analysis of the Use of Interactive Quizzes in Elementary Schools - Wulandari, Retno; Zunaidah, Farida Nurlaila; Sulistiyowati, Tutut Indah (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to analyze the use of interactive quizzes in the learning process in elementary schools. The approach used was descriptive qualitative. The research stages included planning, conducting observations, interviews with teachers and students, distributing needs questionnaires, and reviewing literature from online journals during the 2020–2024 period. Data collection techniques included direct classroom observation, structured interviews, questionnaires, and literature review. The data obtained showed that interactive quizzes such as Bamboozle, Wordwall, and Quizizz have been used in learning, particularly in Indonesian and science subjects. The quizzes were presented in both group and individual formats, with an attractive display that stimulated active student engagement. Teachers stated that interactive quizzes facilitated the delivery of material and improved student understanding. Meanwhile, students felt more enthusiastic and less bored during the learning process. The results of observations and interviews showed that average student grades increased, with scores ranging from 75–95. This finding is supported by literature studies that confirm that interactive media has a positive impact on motivation and learning outcomes. In conclusion, the use of interactive quizzes is an effective and enjoyable learning strategy that can improve the quality of learning in elementary schools.